2022
DOI: 10.3389/fcell.2021.743124
|View full text |Cite
|
Sign up to set email alerts
|

HPS6 Regulates the Biogenesis of Weibel–Palade Body in Endothelial Cells Through Trafficking v-ATPase to Its Limiting Membrane

Abstract: The Weibel–Palade body (WPB) is one of the lysosome-related organelles (LROs) in endothelial cells, whose main content is von Willebrand factor (vWF). The biogenesis of LROs is regulated by the Hermansky–Pudlak syndrome (HPS) protein-associated complexes through transporting cargo proteins to WPBs. Our previous studies have shown that HPS6, a subunit of BLOC-2 complex, is likely involved in the maturation of WPBs. However, the underlying mechanism remains unknown. In this study, we found that the knockdown of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Interestingly, a recent study identified the Hermansky-Pudlak syndrome protein HPS6 as an interaction partner of the V0d1 subunit implicated in mediating a transport of this subunit to WPB. Moreover, depletion of V0d1 in this study resulted in morphological WPB alterations (less elongated) [ 33 ] similar to those observed upon pharmacological V-ATPase inhibition (Figs 2 and 3 ). Thus, inhibition of the proton pump activity of the V-ATPase by pharmacologically targeting a subunit of the V0 subcomplex as well as specific depletion of one of the V0 subunits interferes with WPB acidification and most likely also with proper VWF (and WPB) maturation.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Interestingly, a recent study identified the Hermansky-Pudlak syndrome protein HPS6 as an interaction partner of the V0d1 subunit implicated in mediating a transport of this subunit to WPB. Moreover, depletion of V0d1 in this study resulted in morphological WPB alterations (less elongated) [ 33 ] similar to those observed upon pharmacological V-ATPase inhibition (Figs 2 and 3 ). Thus, inhibition of the proton pump activity of the V-ATPase by pharmacologically targeting a subunit of the V0 subcomplex as well as specific depletion of one of the V0 subunits interferes with WPB acidification and most likely also with proper VWF (and WPB) maturation.…”
Section: Resultssupporting
confidence: 80%
“…In line with this assumption Ma et al described misshaped WPB, similar to the WPB seen NH 4 Cl-treated cells, upon the depletion of HPS6, a subunit of the endosomal BLOC-2 complex, suggesting that endosomes could serve as a further potential source of V-ATPase complexes for WPB [ 41 ]. This view is supported by the recently identified direct interaction between HPS6 and the V0d1 subunit [ 33 ].…”
Section: Resultsmentioning
confidence: 74%
“…Liu et al indicated that TSPYL2 could inhibit SIRT1-mediated FOXO3 deacetylation to reduce gefitinib resistance and inhibit DNA damage, implying that TSPYL2 is a promising therapeutic target ( Liu et al, 2022 ). ATP6V0D1 is an encoded protein involved in vacuolar ATPase formation, which has a crucial role in the modulation of the acidic microenvironment ( Lu et al, 2021 ). Numerous research studies have found that dysregulation of V-ATPase is related to tumor growth and invasion ( Whitton et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The regulated secretion of vWF in Hps6 mutant mice was severely compromised, and the maturation of WPBs was significantly impaired (Ma et al, 2016). Furthermore, HPS6 is required for the trafficking of subunit d1 in the V0 domain of v‐ATPase to the limiting membrane of WPBs to maintain the acidic luminal environment to form highly ordered vWF tubules during its maturation (Lu et al, 2022). These data suggest that HPS6 or BLOC‐2 function in WPB biogenesis and the loss of HPS6 or BLOC‐2 may compromise vWF secretion which is likely contribute to the bleeding tendency.…”
Section: Functions Of Hpacs In the Biogenesis Of Lrosmentioning
confidence: 99%